The Effects of Cellulose on AOM/DSS-Treated C57BL/6 Colorectal Cancer Mice by Changing Intestinal Flora Composition and Inflammatory Factors. (16th March 2021) - Li, Qianqian; Chen, Chen; Liu, Cuiping; Sun, Wenna; Liu, Xiaohan; Ci, Yifan; Song, Yang
Abstract: Chronic intestinal inflammation is a key risk factor of colorectal cancer (CRC). It is known that microbial dysbiosis induces increased inflammatory factors which promote tumorigenesis and cellulose can be beneficial to CRC. In the present study, we investigated the regulatory effects of cellulose on intestinal flora composition and colorectal carcinogenesis in an azoxymethane (AOM)/dextran sulfate sodium (DSS)-induced CRC mouse model. Supplementation of cellulose significantly attenuated inflammation and tumor formation in AOM/DSS-treated CRC mice. The survival rate and the tumor inhibition rate were higher in the medium-dose cellulose group (MCEG) and high-dose cellulose group (HCEG) than in the model group (MG; P < 0.05). Cellulose supplementation stimulated shifts in the intestinal flora in AOM/DSS-treated CRC mice. Additionally, levels of inflammatory mediators involved in colorectal carcinogenesis, such as IL-6, IL-1β, and TNF-α, were lower in the serum of the low-dose cellulose group, MCEG, and HCEG when compared with the MG ( P < 0.05). Whereas the abundance of differential bacteria was correlated with the concentration of IL-6, IL-1β, and TNF-α. These results showed cellulose changed the composition of intestinal flora and inhibited colon inflammation and neoplasm formation caused by the AOM/DSS treatment.